A novel method to produce massive seedlings via symbiotic seed germination in orchids - Yang, Hua; Li, Neng-Qi; Gao, Jiang-Yun (Frontiers in Plant Science, 2023)
Orchids produce large numbers of dust-like seeds that rely heavily on orchid mycorrhizal fungi (OMFs) for germination. Using OMFs to facilitate orchid proliferation is considered an effective method for orchid conservation but still presents challenges in practice. In this study, orchid seed-fungus complexes, in which orchid seeds and fungal mycelia were embedded together to form granules, were developed as platforms to facilitate seed germination and seedling production. Overall, seedlings were produced by seed-fungus complexes for five orchid species with large variations in the percentages of seedlings produced among species/treatments. For the different fungal treatments in Dendrobium officinale, Sebacinales LQ performed much better than the other fungal strains. At 90 days after sowing, 75.8±2.6% seedlings were produced in the LQ treatment, which was significantly higher than in the Tulasnella sp. JM (22.0±3.0%) and Tulasnella sp. TPYD-2 (5.3±1.0%) treatments, as well as in the LQ and TPYD-2 cocultured treatment (40.4±3.2%), while no seedlings were formed in the Tulasnella sp. SSCDO-5 or control treatments. For the other four orchid species, only one compatible fungus for each species was used, and the percentages of seedlings in epiphytic Dendrobium devonianum (67.2±2.9%) and D. nobile (38.9±2.8%) were much higher than those in terrestrial Paphiopedilum spicerianum (2.9±1.1%) and Arundina graminifolia (6.7±2.1%) at 90 days after sowing. Adding 1% polymer water-absorbent resin to the seed-fungus complexes of D. officinale seeds with fungal strain Sebacinales LQ significantly increased seedling formation, while other additional substances showed negative effects on seedling formation. For the storage of seed-fungus complexes, it is recommended to store the seed-fungus complexes in valve bags at room temperature for a short time and at a low temperature of 4°C for no more than 30 days. As a platform for symbiotic seed germination, the seed-fungus complex can facilitate seed germination, produce seedlings and support subsequent seedling growth, and its seedling productivity depends on seed germination characteristics, seed viability, and the efficiency of fungi. Seed-fungus complexes have great potential to be used as propagules in orchid conservation.